Structural engineering, BSA binding and computational analysis of isonipacotate based enzyme inhibitors containing 1,2,4-triazole - Virk, Naeem A.; Aziz-ur-Rehman; Iqbal, Javed; Chohan, Tahir Ali; Alzahrani, Abdullah R.; Jawaid, Talha; Rehman, Zia Ur; Khan, Abida (PLOS ONE, 2026)
Synthetic chemistry facing little difficulties in C–C, C–S, and C–N double bonds activation is a very long-standing challenge. The current studies based on the development of C–N double and single bond, N–N bond and C–S in the trizole and azinane merged rings into single unit. The targeted compounds were obtained through metal free, microwave assisted and conventional techniques. The present work covers sulfonamide, hydrazide synthesis, 1,2,4-triazole, and thioether synthesis to produce piperidine-based triazole analogues (7a-j). An array of electrophiles (6a-j) was treated with 1,2,4-triazole (5) under conventional (59–72% yield) and microwave assisted (87–95% yield) protocols to acquire the targeted molecules (7a-j). The proton and carbon NMR, and IR techniques were used for structural characterization. The analogues (7a-j) were screened against BChE, α-Glucosidase, 15-LOX, and AChE in search for leads compounds. The most active analogues found through IC50 values in μM against AChE were 7h (1.29 ± 1.24), 7c (2.58 ± 1.32) and 7i (5.62 ± 1.35) compared with the standard eserine (0.19 ± 0.05). Compound 7i (2.24 ± 1.80) of the synthesized analogue was found most active against BChE. Compounds against 15-LOX were 7i (2.07 ± 1.17) and 7e (2.12 ± 0.37) found even better than the standard quercetin (2.34 ± 0.35). Most of the synthesized analogues (7a, 7d-7j) showed very excellent potential strength against α-Glucosidase even efficient than reference drug acarbose (38.25 ± 0.12) presented in Table 3. The in vitro results were confirmed by molecular docking investigations of the active ligands with the targeted enzymes. Bovine serum albumin (BSA) binding studies displayed how the ligands interacted with BSA. The data altogether predicts these molecules as leads in search for cholinesterase (7h, 7c, 7i) and 15-LOX (7i) enzymes. Further in vivo work is continued on targeted derivatives of 1,2,4- triazoles as inhibitors of therapeutically important enzymes.